2019
DOI: 10.1055/s-0039-1678537
|View full text |Cite
|
Sign up to set email alerts
|

Midflexion Instability in Primary Total Knee Arthroplasty

Abstract: Instability is one of the most common causes of failure in total knee arthroplasty. Traditionally, it has been classified into three types: extension instability, flexion instability, and hyperextension instability. More recently, a fourth type of instability has been proposed, namely “midflexion instability” (MFI). Whether MFI is distinct from the aforementioned types of instability is contentious, and at present, the condition is yet to be clearly defined. This article reviews the current literature and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Martin and Whiteside 1 defined mid-flexion instability following total knee arthroplasty (TKA) as instability between 0° and 90° in the absence of instability in full extension or in 90° of flexion. Mid-flexion stability is believed to be an important factor influencing successful clinical outcomes following TKA 2-10 .…”
mentioning
confidence: 99%
“…Martin and Whiteside 1 defined mid-flexion instability following total knee arthroplasty (TKA) as instability between 0° and 90° in the absence of instability in full extension or in 90° of flexion. Mid-flexion stability is believed to be an important factor influencing successful clinical outcomes following TKA 2-10 .…”
mentioning
confidence: 99%
“…Their study was unable to demonstrate a significant difference between the two implants, but Hino et al found a greater degree of varus–valgus laxity between 10° and 90° of flexion with posterior stabilised TKRs compared to CR TKRs [ 52 , 53 ]. Long-term outcome studies have not diagnosed mid-flexion instability in both posterior stabilised TKRs and CR TKRs with multi-radius components, though this should be interpreted with caution, as it may well result from under-recognition of mid-flexion instability ( 39 , 42 , 51 54 ). Overall, there is a need for further clinical studies into femoral component design or implants and mid-flexion instability to be able to make any reliable conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…However, postoperative knee instability is not well defined clinically, and the boundaries between stable and unstable TKA knees is still poorly understood. This lack of understanding is likely due to the multitude of factors that are associated knee instability, including inadequate soft tissue balancing (1,2), loss of ligamentous integrity (3), and improper component sizing (3,4).…”
Section: Introductionmentioning
confidence: 99%